(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
The tourism industry faced hyper-competition where visual identity became a vital asset, particularly on digital platforms. Mbarep Tour and Travel struggled with disintegrated visual management, resulting in a low engagement rate of 1.34 percent and significant inconsistencies in typography (70 percent). This research aimed to design an Integrated Visual Identity System as a strategic solution for brand differentiation. The Research and Development method was employed using a hybrid workflow that integrated CorelDRAW for vector precision, Gemini artificial intelligence for mascot three-dimensional enhancement, and Canva for operational templates. The outcome was a comprehensive identity system, including refined logos, standardized typography, and a brand mascot, all codified in a Graphic Standard Manual. Post-implementation results showed 100 percent effectiveness in resolving visual inconsistencies and increased the engagement rate to 1.79 percent. This system successfully transformed the brand into a more professional and competitive entity.